2015
DOI: 10.1093/iwc/iwv032
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Whole-Body Interaction and Design for Museums

Abstract: Museums increasingly use digital technology to enhance exhibition experiences for families, notably in relation to physically mediated installations for young children through Natural User Interfaces. Yet little is known about how families and children engage with such installations and the kinds of interactive experiences they engender in museum spaces. This paper addresses a pressing need for research to adopt an analytical focus on the body during such digitally mediated interactions in order to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Similar to prior work in whole-body interaction [59,62], we found that games were successful in building engagement. This finding extended even to reporters who were not wearing sensors and whose data was not being visualized.…”
Section: Gamessupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to prior work in whole-body interaction [59,62], we found that games were successful in building engagement. This finding extended even to reporters who were not wearing sensors and whose data was not being visualized.…”
Section: Gamessupporting
confidence: 83%
“…As noted in the introduction, though an emerging area, prior work suggests that these computer-mediated, whole-body interactions can promote and support engagement [1,62], immersion [69], sensorimotor development [30], social interaction [59,69] as well as learning (see [31] for a review). Most closely related to our work are the tools STEP [12] and SMALLab [4,26].…”
Section: Embodied Interaction and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the different content displayed, enclosed museum exhibitions often tend to follow general design principles (Hornecker et al, 2014) and thus allow a wide range of advanced interfaces and interaction techniques. Recent studies focus particularly on how visitors' learning experience can be supported during the visit in the museum by interacting with large-scale environments (Flynn, 2013;Kenderdine et al, 2014;Kourakis et al, 2012;Pietroni and Adami, 2014;Price et al, 2015), mobile technologies such as tablets and smartphones (Lanir et al, 2016;Rennick-Egglestone et al, 2013), mobile eye tracking technologies (Mokatren et al, 2016), or smart tangible objects (Marshall et al, 2016). In contrast, in the context of designing for outdoor heritage sites, museum experts often have to consider very specific requirements and constraints (Hornecker et al, 2014), e.g.…”
Section: Related Work 21 Advanced Interfaces For Cultural Heritagementioning
confidence: 99%
“…However, there are still aspects of historical contexts and people's practices in past cultures that are difficult for visitors to imagine (Ciolfi and McLoughlin, 2012). Therefore, there is a growing trend in the exploration of the benefits of ubiquitous computing advanced interfaces (Gena et al, 2016) and context-aware digital augmentation to provide additional information layers within the physical world (Price et al, 2015). In this context, relevant contributions can be found in Augmented Reality (AR) solutions.…”
Section: Introductionmentioning
confidence: 99%